2022
DOI: 10.3390/jcm11195602
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Visual Risk Factors of Anterior Cruciate Ligament Injury of Knee Joint

Abstract: This study aimed to explore whether the defect of visual function is a risk factor of knee anterior cruciate ligament (ACL) sports injury and to provide a theoretical basis for the primary prevention of ACL sports injury. This cross-sectional study included 392 participants divided into two groups: the sports injury group (287 with sports injury of knee) and the control group (105 healthy volunteers). Participants in the sports injury group were further divided into the ACL-Intact group (133) and the ACL-Defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Pivoting, cutting, or jumping sports ( e.g. , basketball, soccer, or team handball) pose an increased risk of anterior cruciate ligament (ACL) injury for athletes ( Chen et al, 2022 ; Reist et al, 2023 ). An earlier study already revealed that female athletes were more susceptible to ACL injuries; the incidence rate in female soccer and basketball players (approximately 5%) was three times higher than that in males ( Prodromos et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pivoting, cutting, or jumping sports ( e.g. , basketball, soccer, or team handball) pose an increased risk of anterior cruciate ligament (ACL) injury for athletes ( Chen et al, 2022 ; Reist et al, 2023 ). An earlier study already revealed that female athletes were more susceptible to ACL injuries; the incidence rate in female soccer and basketball players (approximately 5%) was three times higher than that in males ( Prodromos et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%